The Influence of Profitability, Liquidity and Solvency on Stock Prices in Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2021-2023 - Tjahya, Rizal Indra; Sari, Shintiya Meira Safitri Puspita (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study aims to examine the effect of profitability (EPS), liquidity (CR), and solvency (DER) on stock prices in energy sector companies listed on the Indonesia Stock Exchange during the period 2021 to 2023. The analysis method used is panel data regression with the selection of the best model through the Chow Test, Hausman Test, and Lagrange Multiplier Test, where the results show that the best model used is the fixed effect model. Hypothesis testing is carried out using the t-test (partial), F-test (model feasibility), and Coefficient of Determination Test (Adjusted R²). The results of the t-test show that the EPS variable has a positive and significant effect on stock prices (significance value 0.02), while the CR and DER variables do not have a significant effect on stock prices with significance values ​​of 0.52 and 0.77, respectively. The regression model is declared feasible to use based on the significant F-test results (F = 20.34; sig. 0.00), and the Adjusted R² value of 0.87 indicates that 87% of the variation in stock prices can be explained by the three independent variables in the model. This finding indicates that investors in the energy sector consider the profitability aspect more in making investment decisions, while liquidity and solvency ratios are not dominant factors in determining stock prices.